Comprehensive Study of CoCrCuNi High-Entropy Alloys: Effects of Preparation, Heat Treatment, Computational Simulation, and Alloying Elements - Fachang Zhao; Xingming Zhao; Tianzhi Jiang; Rongda Zhao; Fufa Wu (Metals)
High-entropy alloys have attracted widespread attention from researchers worldwide due to their unique microstructure and outstanding mechanical properties, making them a prominent focus in the field of metallurgy. Among the various high-entropy alloys, the CoCrCuNi system was among the first alloys discovered, and it has shown significant progress in development. By employing different preparation and heat treatment processes, researchers have obtained alloys with diverse performances. The addition of various alloying elements or other components can lead to pronounced variations in the properties of CoCrCuNi high-entropy alloys. This work provides a comprehensive review of recent research progress on CoCrCuNi high-entropy alloys. It covers the preparation methods, thermodynamic and kinetic simulation calculations, as well as discussions on heat treatment processes and the influence of alloying elements on the microstructure and mechanical properties of CoCrCuNi high-entropy alloys. Finally, the review concludes with a prospective analysis and predictions for the potential applications and future directions in developing novel high-entropy alloys.